Multivariate cube integrated retinal variable to visually represent multivariable data - Nguyen, H.T.; Tran, A.V.T.; Nguyen, T.A.T.; Vo, L.T.; Tran, P.V. (EAI Endorsed Transactions on Context-aware Systems and Applications, 2017)
For visualization of multivariable data, multivariate cube meets with the limitation of screen and human vision. Retinal variables are integrated into multivariate cube to enhance its visual characteristics. The selective feature of variables and associative feature of the values of the same variable are improved with the integration of retinal variable into the set of visual variables. The selective, quantitative, and ordered features of the marks of a visual variable are enhanced by the integration of retinal variable into different values. The combination of multivariate cube and retinal variables in data visualization significantly increases visual characteristics. Multivariate cube integrated retinal variable is illustratively applied for visually analyzing the data set of the learning outcomes evaluation of information system curriculum at Thu Dau Mot University and the data set of the happenings of hand, foot, mouth disease in Binhduong province during 2012-